LA FAMILIA Y SU INFLUENCIA EN LOS VALORES DE LOS ESTUDIANTES Y LA INTERVENCIÓN DEL TRABAJADOR SOCIAL. - Vèlez Paccha, Katherine del Carmen (2015)
This research paper entitled "The family and its influence on the values of students and intervention Social Worker"; done at school "Filomena Mora Carrion" city of Loja, contains relevant information and its importance is based on the study of family influence on the values of students through which has shown that students in their It keeps most types of negative behaviors resulting in personal growth and development focusing on the learning of children. The main objective is to strengthen families to purchase securities through Social Intervention with students of the school "Filomena Mora Carrion" parallel 5th year "A" of the city of Loja whose purpose is to use the practice of values with students and Parents. The specific objectives enabled me to carry out actions that facilitated identify theories on the subject of study leading to know and better manage categories, establishing intervention strategies to provide alternative solutions to the research. The research work was based on: Methodology for Community Self, which is used to structure problematize, infer and describe all the steps and results of the research, the first stage is social sharing with the subject appellant of professional action, the second stage exploration stage, the third stage diagnosis and solutions Evaluation fourth stage and the fifth stage: systematization, the first three stages of this research work were used. The techniques used were: observation surveys chips interviews that teachers, parents and students was applied in order to identify the 5 problem "and its influence on family values and student worker intervention social "School" Filomena Mora Carrion "of the city of Loja, in order to obtain adequate information for research. Finally a proposal for strengthening the values and practice of students in the 5th year of basic education parallel "A" school Filomena Mora Carrion, using the entire educational community that comprise principal, students, teachers designed and parents.